ANALISIS SANKSI PAJAK DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DENGAN MODERASI PREFERENSI RISIKO - Nuramalia Hasanah; Mochamad Razief Aditya; Indah Mulyasari (Jurnal Ilmiah Wahana Akuntansi, 2020)
This research aims to determine the effect of tax penalties and tax authority services on taxpayer compliance of individual taxpayer by using risk preference as a moderating variable. Taxpayer compliance is measured by tax penalties, tax authority services and risk preference. The simple random sampling method is used in this research to collect the research sample and obtained as many as 100 respondents. The result shows that the tax penalty's effect on taxpayer compliance. Tax authority services effect on taxpayer compliance, and risk preference effect on taxpayer compliance. The risk preference as a moderating variable has no effect and could not moderate the relationship between tax penalties with taxpayer compliance also between tax authority services with taxpayer compliance.